2021
DOI: 10.3389/fcell.2021.639657
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Applications of Mesenchymal Stem Cells in Idiopathic Pulmonary Fibrosis

Abstract: Idiopathic pulmonary fibrosis (IPF) is an interstitial disease of unknown etiology characterized by progressive pulmonary fibrosis. Pirfenidone and nintedanib are the only drugs that can prolong the time to disease progression, slow down the decline in lung function, and prolong survival. However, they do not offer a cure and are associated with tolerability issues. The pluripotency of mesenchymal stem cells (MSCs) and their ability to regulate immunity, inhibit inflammation, and promote epithelial tissue repa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 124 publications
0
34
0
Order By: Relevance
“…According to the current study, age has become a limiting condition for lung transplantation in IPF patients, and the survival rate after lung transplantation in elderly patients older than 65 years is relatively low ( 108 ). Therefore, it is ofgreat significance to develop effective early diagnostic methods and innovative therapeutic strategies, such as applications of mesenchymal stem cells ( 109 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the current study, age has become a limiting condition for lung transplantation in IPF patients, and the survival rate after lung transplantation in elderly patients older than 65 years is relatively low ( 108 ). Therefore, it is ofgreat significance to develop effective early diagnostic methods and innovative therapeutic strategies, such as applications of mesenchymal stem cells ( 109 ).…”
Section: Discussionmentioning
confidence: 99%
“…To complete this section, we focus in lung fibrosis. Many preclinical and clinical studies using MSCs and their secreted compounds have been performed during the last decade for the treatment of interstitial lung diseases [ 142 , 143 , 144 ]. Several studies describe the anti-inflammatory, microbicidal, angiogenic and antifibrotic effects of MSCs in preclinical studies of pulmonary fibrosis, and the treatment with these cells was able to improve lung function and reduce mortality in rodent models of chronic lung diseases [ 145 , 146 , 147 , 148 ].…”
Section: Mscs As a Treatment Of Several Typical Pathologies Regarding Wound Healingmentioning
confidence: 99%
“…Bone marrow-derived MSCs (BMSCs) possess many advantages, including easier culturing, proliferation, isolation and purification, rendering them convenient for clinical application [ 16 , 17 ]. Many researchers have reported on the clinical use of bone marrow-derived MSCs in the treatment of diseases, including cardiac disease [ 18 ], pulmonary disease [ 19 ], and osteoarthritis [ 20 ]. Recent research identified that exosomes derived from BMSCs can significantly promote the neovascularization and regenerative capacity of promoting tissue repair [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%